Methods of coping with stress in young players in team sports games - Kalinowski, Paweł; Pietranis, Dariusz; Bugaj, Olga; Lachowska, Katarzyna (Journal of Education, Health and Sport, 2017)
Contemporary trends in qualified sport to achieve athletic championship are aimed at constant clarification of the areas of information and the search for new methodological solutions and training. With the ever-rising level of sports, one of the fundamental tasks of theoreticians and practitioners of the sport is the correct diagnosis of sports predispositions of players. Nowadays, sporting success is not determined only by an excellent physical preparation. Players should have corresponding psychological predispositions. One of the psychological aspects relevant to athletes are effective ways of coping with stress. The study attempts to determine the level of how to deal with stress in the representatives of team sports compared with the general population. A survey on ways of coping with stress of 31 players in the younger junior age category appearing in the top division was carried out using a CISS questionnaire created by Norman and Parker (1990), adapted by Polish authors (Strelau et al. 2005). The results showed that young athletes were characterized by a lower level of styles and strategies focused on emotions compared with those of the general population and a higher level of ways of focusing on the task compared with the general population. The observed differences were statistically significant.